2008
DOI: 10.1007/s11999-008-0254-z
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Tendinopathy With Injections of the MMP-inhibitor Aprotinin

Abstract: Aprotinin is a broad spectrum proteinase inhibitor (including matrix metalloproteinase [MMP] inhibitor) used for treating patellar and Achilles tendinopathies. One previous randomized control trial demonstrated aprotinin injections superior to both corticosteroid and saline injections in patellar tendinopathy (Level II), whereas results reported for aprotinin treatment in Achilles tendinopathy have been mixed. We performed a case review and followup questionnaire for 430 consecutive patients with tendinopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 29 publications
0
57
0
2
Order By: Relevance
“…81,97 Although enzyme inhibitors have not been extensively evaluated in the treatment of tendinopathy, 2 small trials have ascertained whether patients with patellar and Achilles tendinopathy may benefit after peritendinous injections of aprotinin, a general protease inhibitor, 74 but further evidence of its efficacy has been shown in a large case series on chronic tendinopathy. 86 In a small, randomized trial of patients with Achilles tendinopathy, combined treatment with aprotinin and eccentric exercises did not significantly improve outcomes compared with placebo, although results in both groups were satisfactory. 17 Despite the theoretic benefits and this low level of evidence, aprotinin is no longer available in most countries to use as an injectable MMP inhibitor (in small doses).…”
Section: Mmps In Tendinopathymentioning
confidence: 93%
“…81,97 Although enzyme inhibitors have not been extensively evaluated in the treatment of tendinopathy, 2 small trials have ascertained whether patients with patellar and Achilles tendinopathy may benefit after peritendinous injections of aprotinin, a general protease inhibitor, 74 but further evidence of its efficacy has been shown in a large case series on chronic tendinopathy. 86 In a small, randomized trial of patients with Achilles tendinopathy, combined treatment with aprotinin and eccentric exercises did not significantly improve outcomes compared with placebo, although results in both groups were satisfactory. 17 Despite the theoretic benefits and this low level of evidence, aprotinin is no longer available in most countries to use as an injectable MMP inhibitor (in small doses).…”
Section: Mmps In Tendinopathymentioning
confidence: 93%
“…Aprotinin, a broad spectrum serine protease inhibitor, has been used successfully in the management of tendinopathy. 21 It has indeed been observed that some proteases may be essential in healthy tendons, as well as tendons undergoing repair. 22 The test platform that we developed could be used to help differentiate which proteases should be inhibited.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…MMP inhibitors such as aprotinin may control the cycle of degradation and repair. There are conflicting reports of the efficacy of peritendonous injection of aprotinin in treatment of patellar and Achilles tendonopathy [28]. A randomised controlled trial (RCT) of Achilles tendonopathy did not show any significant improvement in outcome for patients treated with aprotonin vs placebo [29].…”
Section: Aprotininmentioning
confidence: 99%